(untitled) (Research, Society and Development, 2021)
Objective: Report the concomitance of two cardiomyopathies: Hypertrophic cardiomyopathy and Left ventricular noncompaction on a 27 years old patient. Method: Literature research and comparison with the case report. Results: Hypertrophic cardiomyopahty is the most common genetic cardiac disease, instead of Left ventricular noncompaction, that is a rare genetic cardiac disease. The evaluation of the reported case showed the presence of those two diseases, simultaneously. Conclusions: It is important to look at the fact that the patient showed only difficult breathing to medium and great efforts; but was diagnosed a rare disease in the concomitance of another cardiomyopathy; the treatment chosen was the implantation of a implant cardioverter defibrillator, because of it’s indication on the two diseases.